Pharmacists’ Recommendations to Improve Care Transitions - Haynes, Katherine Taylor (2012)
BACKGROUND: Increasingly, hospitals are implementing multi-faceted programs to improve medication reconciliation and transitions of care, often involving pharmacists. OBJECTIVE: To help delineate the optimal role of pharmacists in this context, this qualitative study assessed pharmacists’ views on their roles in hospital-based medication reconciliation and discharge counseling. We also provide pharmacists’ recommendations for improving care transitions. METHODS: Eleven study pharmacists at two hospitals who participated in the Pharmacist Intervention for Low Literacy in Cardiovascular Disease (PILL-CVD) study completed semi-structured one-on-one interviews, which were coded systematically in NVivo. Pharmacists provided their perspectives on admission and discharge medication reconciliation, in-hospital patient counseling, provision of simple medication adherence aids (e.g., pill box, illustrated daily medication schedule), and telephone follow-up. RESULTS: Pharmacists considered medication reconciliation, though time-consuming, to be their most important role in improving care transitions, particularly through detection of errors in the admission medication history that required correction. They also identified patients with poor understanding of their medications, who required additional counseling. Providing adherence aids was felt to be highly valuable for patients with low health literacy, though less useful for patients with adequate health literacy. Pharmacists noted that having trained administrative staff conduct the initial post-discharge follow-up call to screen for issues and triage which patients needed pharmacist follow-up was helpful and an efficient use of resources. Pharmacists’ recommendations for improving care transitions included clear communication among team members, protected time for discharge counseling, patient and family engagement in discharge counseling, and provision of patient education materials. CONCLUSION: Pharmacists are well-positioned to participate in hospital-based medication reconciliation, identify patients with poor medication understanding or adherence, and provide tailored patient counseling to improve transitions of care. Additional studies are needed to confirm these findings in other settings, and to determine the efficacy and cost-effectiveness of different models of pharmacist involvement.